A new species of cascade frog (Amphibia: Ranidae) in the Amolops monticola group from China - Yuan, Zhiyong; Jin, Jieqiong; Li, Jiannan; Stuart, Bryan L.; Wu, Jun (Zootaxa, 2018)
A new species, Amolops wenshanensis sp. nov., is described from Guangxi and Yunnan Provinces, China. The new species is a member of the A. monticola group, and is distinguished from its congeners using morphological and molecular data. The new species is diagnosed by having glandular dorsolateral folds; smooth skin; side of head dark with a light-colored upper lip stripe extending to axilla; green dorsal coloration in life; immaculate venter; indistinct transverse bands on dorsal surfaces of limbs; tympanum distinct; pineal body absent; all fingertips expanded with circummarginal grooves; two oblique vomerine teeth; vocal sac and white nuptial pad present in males; supratympanic fold absent; outer metatarsal tubercle absent; glandular gold-white flank spot absent; and skin on venter not translucent. A molecular phylogenetic analysis is performed using the mitochondrial (mt) NADH dehydrogenase subunit 2 (ND2) gene and parts of flanking tRNA genes for nine of the 15 members of the A. monticola group with available homologous sequences. The new species is sister to a clade containing A. cucae and A. compotrix, two species known from adjacent parts of Vietnam and Laos. The new species differs from its congeners by having an uncorrected p-distance of > 6.7% in the mt DNA fragment examined. At present, the new species is known from small, montane streams near Wenshan, Yunnan Province, and Jingxi, Guangxi Province, China.